2021
DOI: 10.1017/s0960258521000234
|View full text |Cite
|
Sign up to set email alerts
|

How regional climate and seed traits interact in shaping stress–tolerance of savanna seeds?

Abstract: Functional traits related to regeneration responses to the environment are highly determinants of distribution patterns of plant communities. A large body of studies on seed traits suggests that regional climate may act as a strong filter of plant recruitment; however, few studies have evaluated the relative importance of seed traits and environmental filters for seed persistence at the population level. We tested the role of seed mass, water content and desiccation tolerance, as well as the germination time a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 79 publications
1
0
0
Order By: Relevance
“…Given the rapid rate of climate change in the region and the high degree of habitat fragmentation throughout the Klamath Mountain and Willamette Valley ecoregions (Floberg et al, 2004), seeds sourced from the south may have been of a generally inferior quality than northern seeds, possibly linked to greater climate-related environmental stresses at lower latitudes. Other studies have found that climate-based environmental stresses lead to decreased germination (Oliveira et al, 2019;Ribeiro et al, 2021;Yi et al, 2019), which may help explain our finding that northern seeds outperform southern seeds at both common gardens.…”
Section: Latitude Did Not Drive Seedling Emergence Patternssupporting
confidence: 70%
“…Given the rapid rate of climate change in the region and the high degree of habitat fragmentation throughout the Klamath Mountain and Willamette Valley ecoregions (Floberg et al, 2004), seeds sourced from the south may have been of a generally inferior quality than northern seeds, possibly linked to greater climate-related environmental stresses at lower latitudes. Other studies have found that climate-based environmental stresses lead to decreased germination (Oliveira et al, 2019;Ribeiro et al, 2021;Yi et al, 2019), which may help explain our finding that northern seeds outperform southern seeds at both common gardens.…”
Section: Latitude Did Not Drive Seedling Emergence Patternssupporting
confidence: 70%